Assessing the Degree of International Consumption Risk Sharing - Hevia, Constantino; Serven, Luis (World Bank, Washington, DC, 2016)
This paper examines the extent of consumption risk sharing for a group of 50 high-income and developing countries. The analysis is based on the empirical implementation of a model of partial consumption insurance whose parameters have the natural interpretation of coefficients of partial risk sharing even when the 0 hypothesis of perfect risk sharing is rejected. The estimation results show that high-income countries exhibit higher degrees of risk sharing than developing countries, and that the gap between the two country groups appears to have widened over the period of financial globalization. Moreover, the pattern of consumption risk sharing is related to the degree of financial openness: countries with more open capital accounts, and larger stocks of foreign assets and liabilities exhibit larger degrees of risk sharing. Yet, larger countries in terms of gross domestic product show lower degrees of consumption risk sharing.